1999
DOI: 10.1034/j.1399-3003.1999.13f30.x
|View full text |Cite
|
Sign up to set email alerts
|

Personally measured weekly exposure to NO2 and respiratory health among preschool children

Abstract: Nitrogen dioxide is known as a deep lung irritant. The aim of this study was to find out whether the relatively low ambient air NO2 concentrations in the northern city of Helsinki had an impact on the respiratory health of children. The association between personal exposure to ambient air NO2 and respiratory health was investigated in a 13-week follow-up study among 163 preschool children aged 3-6 yrs. Personal weekly average exposure to NO2 was measured by passive diffusion samplers attached to the outer garm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This result is corroborated by other panel studies in children with distinct outcomes, such as cough and respiratory symptoms. 12 In contrast, among children younger than 18 months of age, this association between exposure to NO 2 and respiratory problems was not observed. 19 Different results show that other studies need to assess the impact of NO 2 on child lung function.…”
Section: Discussionmentioning
confidence: 60%
“…This result is corroborated by other panel studies in children with distinct outcomes, such as cough and respiratory symptoms. 12 In contrast, among children younger than 18 months of age, this association between exposure to NO 2 and respiratory problems was not observed. 19 Different results show that other studies need to assess the impact of NO 2 on child lung function.…”
Section: Discussionmentioning
confidence: 60%
“…In Helsinki, nasal congestion occurred on more days among children living in central than in suburban areas, and was related to their personal exposure to NO 2 , attributed to proximity of automobile traffic. 30 A study of volunteers found that the most prominent symptoms during exposure to diesel exhaust were irritation of the eyes and nose and an unpleasant smell. 31 These reports accord with the findings of the present study, where the greatest net improvement in the health of residents of the congested streets was in terms of rhinitis and rhinoconjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the sociodemographic characteristics between those children included in or those excluded from final analyses, except smoking at home in the central area. 34 We used the 25th and 75th percentiles of the exposure distribution as cutpoints for each of the four exposure assessment methods to estimate NO2 exposure. Other categorizations were also tested, but the conclusions from these analyses remained consistent with those presented.…”
Section: Methodsmentioning
confidence: 99%